SH1 leaf rust and bacterial halo blight coffee resistances are genetically independent - Lucas Mateus Rivero Rodrigues (Bragantia, 2017)
Coffee resistance to Pseudomonas syringae pv. garcae has been associated to pleiotropic effect of SH1 allele, present in coffee plants resistant to certain races of Hemileia vastatrix, the causal agent of leaf rust, or genetic linkage between resistance alleles to both pathogens. To validate this hypothesis, 63 coffee plants in F2 generation were evaluated for resistance to 2 isolates of H. vastatrix carriers of alleles, respectively, v2, v5 (isolate I/2015) and v1; v2; v5 (isolate II/2015) with the objective to confirm presence of SH1 allele in resistant plants to isolate I/2015. The same coffee plants were evaluated for resistance to a mixture of P. syringae pv. garcae strains highly pathogenic to coffee. Results showed that, among F2 coffee allele SH1 carriers, resistant to isolate I/2015, resistant and susceptible plants to bacterial halo blight were found; the same segregation occurs between F2 homozygous for SH1 allele, susceptible to the same isolate (I/2015) of H. vastatrix. Results also indicate that there is no pleiotropic effect of gene or allele SH1 connection between genes conferring resistance to leaf rust caused by H. vastatrix and bacterial halo blight caused by P. syringae pv. garcae.